La scoperta del paesaggio terrestre. Note sulla rivoluzione spaziale astronautica del paesaggio - Morawski, Tommaso (Aesthetica Preprint, 2024)
The most important event in cosmonautical exploration was not the reaching of distant lunar territory, but the fact that the Earth for the first time had the opportunity to see itself, to meet itself. Two photographs in particular have imposed themselves as a true visiotype of our planetary imagination, establishing the birth of a new landscape consciousness of the cosmos: Earthrise (1968) and The Blue Marble (1972). This article analyses the landscaping operation from which the new astronautical worldview originated: that “altered image of the Earth” that represents the most important and lasting legacy of the ‘astronautical spatial revolution’, the last great global spatial revolution in the air age.